Retrieval of lunar polar heat flow from Chang’E-2 microwave radiometer and Diviner observations - Wei, Guangfei; Li, Xiongyao; Gan, Hong; Shi, Yaolin (Frontiers in Astronomy and Space Sciences, 2023)
The internal heat flow related to the Moon’s composition, interior structure, and evolution history is not well-constrained and understood on a global scale. Up to now, only two in situ heat flow experiments, Apollo 15 and 17 were deployed nearly 50 years ago. The measured high values of heat flow might be influenced by lateral heat at highland/mare boundaries and enhanced by heat production from radioactive elements enriched unit, and may also be disturbed by astronauts’ activities. In this study, we proposed a new method to retrieve heat flows at two permanently shadowed craters, Haworth and Shoemaker of the Moon’s south pole, from Chang’E-2 Microwave Radiometer data and Diviner observations. Our results show that the average heat flow is 4.9 ± 0.2 mW/m2. This provides a constraint for the bulk concentration of Thorium within the lunar south polar crust 656 ± 54 ppb, which helps us understand the Moon's thermal evolution and differentiation.